A Survival Analysis of Breast Cancer Patients at Andalas University Hospital from 2019 to 2023 - Yeffi Masnarivan; Muchtariza, Suci; Widoyo, Ratno (LPPM Universitas Prima Nusantara Bukittinggi, 2026)
Background: Breast cancer is one of the leading health problems among women worldwide, including in Indonesia. More than 80% of cases in Indonesia are diagnosed at an advanced stage and are associated with low survival rates. Objective: This study aims to analyze the survival of breast cancer patients at Andalas University Hospital from 2019 to 2023. Methods: This study employed a retrospective cohort design. Secondary data were collected from breast cancer patients at Andalas University Hospital between 2019 and 2023. A total of 52 breast cancer patients were selected using simple random sampling. The data were analyzed using survival analysis methods, including the log-rank test, Kaplan–Meier curves, and Cox regression. Results: During the five-year observation period, 63.5% of patients experienced the event of interest. Most breast cancer patients at Andalas University Hospital from 2019 to 2023 were over 45 years old (75.0%), unemployed (69.2%), diagnosed at clinical stage IV (40.4%), had anemia (51.9%), and received combination therapy (59.6%). A significant association was found between cancer stage and patient survival. However, age, employment status, type of treatment, and anemia status were not significantly associated with breast cancer patient survival.